THE IMPORTANCE OF PLAYING FOR CHILDREN’S COGNITIVE AND PSYCHOMOTOR DEVELOPMENT - Martins da Silva, Elizabete; Felix Oliveira, Silvana; Paulo Pereira, Rosimary; Pereira da Silva, Zenaide; do Socorro Almeida Angelo Segunda, Maria (Revista Gênero e Interdisciplinaridade, 2024)
Playing has been part of people’s lives since ancient times, being an important learning mechanism. Therefore, it is necessary to observe and take into account its real importance in child development. Playing in a playful way builds knowledge, with play being an extraordinary way to develop learning and build a child’s real world. However, playing stimulates the improvement of children’s motor skills and functions as inexhaustible sources of promoting playfulness, affection and education. Through games, games and recreational activities, they exercise their cognitive skills, such as problem solving, creativity, imagination and concentration. Furthermore, playing at school can contribute to social interaction and the building of healthy relationships between children. Educators and education professionals must understand the importance of playing and know how to integrate it appropriately into the school curriculum. This involves creating spaces for play, selecting appropriate materials and toys, developing instructional recommendations that emphasize play, and active teacher involvement in guidance and mediation activities.